Peran nutrasetikal dalam tatalaksana diabetes melitus type 2: mini review - Tri Kusuma Agung Puruhita; Debby Endayani Safitri; Nur Setiawati Rahayu (UHAMKA PRESS, 2022)
Diabetes mellitus Type 2 (DMT2) is a metabolic syndrome disease characterized by high blood glucose levels. DMT2 increases the risk of complications that lead to death. One of the modifiable risk factors to reduce the incidence and severity of diabetes is diet. Intake of bioactive compounds in the diet can reduce the risk of developing DMT2. There are many food ingredients, which contain bioactive components, to help maintain blood sugar levels such as bitter melon, fenugreek, ginseng, cinnamon, and saffron. This review was conducted with the aim of providing an overview of the various bioactive components in foodstuffs and their mechanism of action in the management of DMT2. This review was conducted by analyzing various journal databases such as Pubmed and scholar with the keywords nutraceutical and DMT2. Based on the reviews that have been carried out, it was found that several types of food such as bitter melon, ginseng, cinnamon, fenugreek, and saffron have benefits in reducing the risk of developing DMT2 by maintaining blood sugar levels.